2018
DOI: 10.3390/fermentation4030066
|View full text |Cite
|
Sign up to set email alerts
|

Application of Non-Saccharomyces Yeasts Isolated from Kombucha in the Production of Alcohol-Free Beer

Abstract: Alcohol-free beer (AFB) is no longer just a niche product in the beer market. For brewers, this product category offers economic benefits in the form of a growing market and often a lower tax burden and enables brewers to extend their product portfolio and promote responsible drinking. Non-Saccharomyces yeasts are known for their flavor-enhancing properties in food fermentations, and their prevailing inability to ferment maltose and maltotriose sets a natural fermentation limit and can introduce a promising ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 48 publications
(43 reference statements)
8
70
0
7
Order By: Relevance
“…Torulaspora delbrueckii is another versatile yeast suitable for beer production [62], as it exhibits low alcohol production ability [94] due to its inability to utilize maltose [95]. This strain has the added advantage of being resistant to the various stress factors encountered during brewing [87] and to produce 2-phenyl ethyl acetate, a floral ester with positive floral aroma, that increases during fermentation [62].…”
Section: New Trends Regarding Yeasts Involved In Fermentation Of Specmentioning
confidence: 99%
“…Torulaspora delbrueckii is another versatile yeast suitable for beer production [62], as it exhibits low alcohol production ability [94] due to its inability to utilize maltose [95]. This strain has the added advantage of being resistant to the various stress factors encountered during brewing [87] and to produce 2-phenyl ethyl acetate, a floral ester with positive floral aroma, that increases during fermentation [62].…”
Section: New Trends Regarding Yeasts Involved In Fermentation Of Specmentioning
confidence: 99%
“…Traditional fermented beverages could also be an important source of new strains of non‐ Saccharomyces yeasts for the production of alcohol‐free beers. Bellut et al () showed the highest potential of a Zygosaccharomyces bailii strain, isolated from Kombucha, in the brewing of alcohol‐free beer. In addition to its inability to ferment maltose and maltotriose, it was able to grow at high iso‐α‐acid concentrations, was POF negative, and was moderately flocculent, and the final beer was slightly fruitier and had low level of worty character.…”
Section: Repurposing Of Yeasts From Different Food and Beveragesmentioning
confidence: 99%
“…Substances like hop-derived iso-α-acids, ethanol content, or the pH value of the wort can have significant influences on yeast activity, manifesting mainly in a prolonged lag time, and even complete growth inhibition [33][34][35]. With the investigated yeast strains, iso-α-acid concentrations of up to 100 IBU had no significant effect on the yeast growth (data not shown), which is in accordance with previous reports on seven different non-Saccharomyces species [34,35]. However, Michel et al [33] reported a minor prolongation in the lag time of Torulaspora delbrueckii strains in concentrations of up to 90 IBU.…”
Section: Stress Testsmentioning
confidence: 99%
“…To investigate interspecific differences in the fermentation of wort, fermentation trials were performed in a diluted wort extract of 7 • P. Previous studies have shown that extract contents of around 7 • P will yield ethanol concentrations of around 0.5% ABV, a popular legal limit for NAB [7], in fermentations with maltose-negative yeast strains [1,14,34,38]. After aerobic propagation for 24 hours, NT Cyb exhibited the highest number of cells, at 2 × 10 9 cells/mL, more than four-fold the amount of cells compared to L1, C6.1, and the CBS strains with counts between 3.4 and 4.9 × 10 8 cells/mL (Table 6).…”
Section: Screeningmentioning
confidence: 99%